III-Nitride Emitters and Converters: Built-in polarization-induced electric fields, built-in potential, and effective doping concentration - Ρουμελιώτης, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2017)
The internal electric fields and the electro-optical response of nearly lattice-matched InGaN/GaN and InAlN/GaN heterostructures were experimentally quantified. Capacitance-Voltage (CV) measurements were performed on PIN diodes based on InGaN/GaN and InAlN/GaN quantum wells grown on (0001) sapphire substrates by metalorganic vapour phase epitaxy (MOVPE). Large polarization fields dependent on the indium content were quantified on In0.055Ga0.945N/GaN (-2.25 ± 1.25 MV/cm) and In0.17Al0.83N/GaN (5.90 ± 3.10 MV/cm), In0.20Al0.80N/GaN (5.99 ± 2.76 MV/cm), In0.22Al0.78N/GaN (5.26 ± 1.25 MV/cm) based heterostructures and associated with the electro-optical properties of the PIN diodes studied by electroreflectace (ER) and electroluminescence (EL) spectroscopy. The electro-optically modulated field (0.04 MV/cm) was determined from Franz-Keldysh Oscillations (FKOs) related to the barrier regions of the InGaN/GaN QW heterostructure. The internal field strength and direction were in agreement with theoretical predictions.